Educational Policies in Southern Europe: The impacts of the financial crisis in a comparative perspective - Sebastião, João; Capucha, Luís; Martins, SC; Capucha, A. (XII Congreso Español de Sociología: Grandes Transformaciones Sociales, Nuevos Desafíos Para La Sociología, 2016)
This presentation discusses the impacts of the financial crisis in the educational systems of the southern European countries, specifically if these systems were affected in its capacity to provide equal educational opportunities. To do so a large set of quantitative indicators were collected from international databases and qualitative data provided by each national team involved in the study “Educational Challenges in Southern Europe. Equity and efficiency in a time of crisis”, developed in CIES-Instituto Universitário de Lisboa. Starting from the specific characteristics and evolution of the results and performance of their educational systems within the European context we’ve looked for to answer if and how the economic/financial crisis has impacted on equity and quality in education systems in southern Europe; which were the tendencies of change and if, in consequence, these educational systems are becoming more selective. The analysis of the educational policies and of the main educational results, over the period of 2000-2013/14, allowed identifying some specific tendencies in this period: • A clear pathway of convergence of the four countries towards the average European educational levels, although with significant differences among them; • The existence of a limited set of political measures specifically to confront the budgetary impacts of the crisis; • The relevant role of the national political cycles, which allowed the implementation of educational policies that until there were clearly a minority, and that cannot be associated with the adjustment process resulting from the crisis; • In general the trend to reverse the process of convergence, albeit with significant national variations,; In the end, one of the strongest conclusions is that the ideological position of the Governments constituted a decisive factor in the way how the educational measures were considered, many of them unrelated to the effort of budgetary control, but particularly geared to the implementation of selective measures (Portugal and Spain), improvement of the educative inclusion processes (Italy) and with little impact on educational situation prior to the crisis (Greece).